2008
DOI: 10.1021/cg800657k
|View full text |Cite
|
Sign up to set email alerts
|

Protein−Salt−Water Solution Phase Diagram Determination by a Combined Experimental−Computational Scheme

Abstract: A continuously fed microfluidic chamber has been developed for determination of solution phase diagrams for protein−precipitant systems. Laminar flow and diffusion in the chamber create significant gradients in concentration, so crystals form in only part of the chamber. By combining observation of the location of the crystal-rich regions with a computer simulation of flow and transport in the chamber, a solution phase diagram is generated. The device was tested successfully on the well-studied lysozyme−NaCl−w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…13 We established that the discrepancy between on-chip and macroscopic sample behavior observed here did not result from potential inaccuracies in the ratio of volumes of chambers. At the same time, the value of 173 Å is at variance with previously reported lattice parameters of Pn3m cubic phases of MO mixed with detergent solutions, 13,14,33 which typically do not exceed 135–145 Å under conditions similar to ours.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…13 We established that the discrepancy between on-chip and macroscopic sample behavior observed here did not result from potential inaccuracies in the ratio of volumes of chambers. At the same time, the value of 173 Å is at variance with previously reported lattice parameters of Pn3m cubic phases of MO mixed with detergent solutions, 13,14,33 which typically do not exceed 135–145 Å under conditions similar to ours.…”
Section: Resultssupporting
confidence: 78%
“…Although microfluidic platforms for phase behavior studies have been demonstrated, 2541 reported systems are only applicable to low-viscosity solutions and typically rely on phase transitions driven by composition changes due to diffusion of solutes, 25,26,3336 evaporation of water, 2832,4042 and osmotic stress. 37,38 Such platforms are not suitable for the formulation of viscous mesophases with strict pre-set ratios of volume or weight of components.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microevaporationbased approaches with a single initial phase of liquid without a carrier phase by precise pumping to control the evaporation rate have also been used (48,49). Flow-through approaches are also common where either droplets (50) or slugs of liquid (51)(52)(53) change phase rapidly while moving in a channel due to the thermodynamic conditions of the system. Other studies have employed co-flow-based systems in which the position of the interface determines the phase equilibrium (54,55).…”
Section: Pdms: Poly(dimethylsiloxane)mentioning
confidence: 99%
“…Such limitations may be overcome by the suitable application of fluid flows that promote mass transfer of the solute via convection. Much experimental work has been devoted to this topic [24][25][26][27][28][29][30][31][32][33], and we have carried out extensive modeling studies of solution crystal growth systems [34][35][36][37][38][39][40][41][42][43][44].…”
Section: Increasing Growth Rates In Solution Crystal Growth Via Applimentioning
confidence: 99%